Model of the planning process under the conditions of anti-crisis management - E. V. Emeljanova (Путеводитель предпринимателя)
This article presents the stages of the planning process under the conditions of anti-crisis management, defines the requirements for the formation of the planning indexes and also the specialties of the range indexes formation at the crisis period in companies.